PATTERN AND BURDEN OF VARIOUS MYTHS REGARDING POLIO VACCINE AMONG THE PARENTS OR LEGAL GUARDIANS WHO REFUSED POLIO VACCINATION TO THEIR CHILD - TUFAIL , N; JAMIL , MF; IJAZ , B; USMAN, A; SHAHEEN , A; NAQVI , SAA (Biological and Clinical Sciences Research Journal, 2023)
Polio is still prevalent worldwide and is yet to be eradicated from Pakistan despite the best efforts of various national and international organizations such as WHO, UNICEF, and UNESCO. A study was conducted to determine the different myths surrounding polio vaccination among parents or legal guardians who refused to vaccinate their children. The study aimed to identify the pattern and burden of various myths regarding the polio vaccine among the parents or legal guardians who refused polio vaccination to their children. This descriptive cross-sectional study was conducted at the Department of Community Medicine, Nishtar Medical University, Multan, in major areas of Multan City from June 25, 2022, to June 24, 2023. Field visits were made to the homes of parents or legal guardians of households who refused polio vaccination on the last 2 consecutive campaigns by EPI. Of the 241 respondents, 154 (63.9%) were males, and 87 (36.1%) were female respondents. The mean age of the study cases was 31.12 ± 4.59 years. The mean number of children was 4.12 ± 1.02, ranging from a minimum of 2 to a maximum of 7. Most of the study participants were illiterate, with only 12 % having education up to the matriculation level, and none having educational level more than matriculation. Of the 241 study cases, 87 (36.1 %) were jobless, 32% were laborers, 12.4% were shopkeepers, 3.7 % had their own business, 11.6 % were farmers, and 4.1 % had private jobs. Of the 241 study participants, 4.1% were Urdu speaking, 23.7% were Punjabi, 44 % were Saraiki, 15.8% were Baloch, and 12.4% were Pathans. The study results showed that 16.6% of the participants reported that the vaccine was unnecessary, and 52.3% reported that the vaccine was harmful. Most parents or guardians who refused to vaccinate their children against the polio virus believed that the vaccine was harmful and unnecessary. The myth that the vaccine is harmful and will make their child sterile was more prevalent. In contrast, the myth that the vaccine is unnecessary was significantly associated with the gender of respondents, education, socioeconomic status, occupation, and ethnicity. On the other hand, the myth that the vaccine is harmful was significantly associated with increasing age, socioeconomic status, education, occupation, and ethnicity.